Pengaruh Pelayanan dan Kualitas Produk terhadap Pertumbuhan Usaha dimoderasi oleh Kepuasan Pelanggan - Ari Soetiyani; Adeliya Indir Maida (J-MAS (Jurnal Manajemen dan Sains), 2022)
This study aims to determine the effect of service quality, product quality, customer satisfaction on business growth for consumers of Kebalen Catfish, Bekasi. The population in this study was 78 respondents who participated in filling out questions in the form of a questionnaire. This research method uses a quantitative approach and also uses the SmartPLS application to calculate validity and hypotheses. From the results of this study that the quality of service and customer satisfaction can have a significant effect and the hypothesis is accepted. Meanwhile, product quality has no significant effect and the hypothesis is not accepted. So it is hoped that the owner of the Kebalen Catfish business in Bekasi can maintain better product quality in order to increase business growth.